Hubungan Ilmu dengan Nilai-Nilai dalam Pengelolaan Sumber Daya Manusia Sebagai Basis Pengembangan Teori dan Konsep Manajemen Pendidikan Islam - Nikmatul Khoiriah; Susanto Susanto (Ikatan Dai Indonesia, 2026)
This study aims to analyze the relationship between knowledge and values in human resource management (HRM) as the foundation for developing theories of Islamic educational management. The study is motivated by a value crisis in modern management, which prioritizes efficiency over moral and spiritual dimensions. In Islam, knowledge and values are inseparable; knowledge provides rational direction, while values offer ethical and spiritual guidance to ensure that knowledge aligns with divine principles. Using a qualitative approach with a library research method, the data were drawn from academic literature, Qur’anic interpretations, and scholarly works on Islamic educational management. The findings indicate that the integration of knowledge and values forms a holistic concept of Islamic management—rational, moral, and spiritual. Management functions such as planning, organizing, implementing, and controlling should be based on Qur’anic principles like tawhid, amanah, ‘adl, and ihsan. The conceptual model—knowledge, values, policy, behavior, and institutional quality shows that Islamic HRM aims not only for effective performance but also for the formation of faithful, knowledgeable, and ethical individuals.